Ovarian cryopreservation and transplantation: A preserving fertility procedure - Bram Pradipta; . Rajuddin; Mohd Andalas (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Cancer is a major health problem in both developed and developing countries. In women, cancer incidence rates increased every year. Developments in treatment modalities and the ability to detect tumours in the early stages increased their survival rate but also raise fertility problems. Those problems are the fertility preservation for patient who have to endure gonadotoxic chemotherapy and or radiation even though they still need their fertility functions. Ovarian cryopreservation and autotransplantation were initially designed to protect and restore reproductive function in patients receiving sterilizing chemotherapy and/or radiotherapy. Other indications including patients undergoing haematopietic stem cell transplantation, autoimmune diseases and those undergoing oophorectomy for non-cancer conditions. Options in cryopreserved ovarian tissues include autotransplantation and xenotransplantation. An orthotopic site or a heterotopic site can be considered for autotransplantation. Xenotransplantation of human ovarian tissue into immunodeficient animals can prevent immunological rejection.  The theoretical advantage of orthotopic grafts is the restoration of normal reproductive function and natural conception after transplantation but application for cancer patients is problematic because of the potential risk of transmission of microscopic metastatic disease. With Xenotransplantantion, the possibility of cancer transmission and relapse can be eliminated because cancer cells cannot penetrate the zona pellucida, and some technical difficulties of in vitro growth and maturation of primordial follicles can be bypassed. But it is still unknown whether conditions for the growth and maturation of human oocytes in an animal host are comparable to those in situ and whether animal pathogens can be transmitted to human tissue with it. Ovarian tissue cryopreservation is the fertility preservation option for prepubertal girls and for women who face thehigh likelihood of diminished ovarian reserve requiring immediate treatment. Its procedure are still within improvement and also in the study of understanding its mechanism. In the future, studies and large clinical trials are still needed to develop better cryoprotectants and cryopreservation protocols and also standardization - optimization transplantation techniques